Virtual Communicative Review of Children’s Art Schools of Irkutsk Region - Dvorovenko Olga (Виртуальная коммуникация и социальные сети)
Children’s art schools use virtual accounts to promote their activities, teachers’ achievements, curriculum, services, and events. The author studied twelve accounts of children’s art schools located in the Irkutsk Region to evaluate the advertising options that virtual space offers to this category of education establishments. The research covered publications made in VKontakte social network between September 18 and October 18, 2024. It revealed a set of statistical indicators that demonstrated subscribers’ engagement and the most relevant topics, e.g., news, upcoming events, curriculum, local culture, etc. The most popular publications included information about teachers, students’ achievements, and art school projects. Most accounts owed their high engagement rates to diverse content and high subscribers’ activity. The communities of the Tulun children’s art school and children’s music school showed very high levels of engagement. The highest engagement levels belonged to the children’s art and music schools in Tulun. These schools used social nets to promote their education programs and broadcast achievements of theirstudents and teachers. The accounts with high engagement rates became involved in social media recommendation algorithms.